MASS INDEPENDENTLY FRACTIONATED SULFUR COMPONENTS IN CHONDRITES - Rai V.K.; Thiemens M.H. (My University, 2007)
We report high precision sulfur isotopic data obtained by sequential extraction from various physically separated phases (bulk, matrix, and chondrules) from chondrites. A significant excess of 33S (up to Δ33S of 0.112‰ for Dhajala Chondrule) has been observed and is most likely carried by chondrule rims, though chondrule interiors cannot be ruled out as a carrier. Stellar nucleosynthesis and spallation are ruled out as a cause for this anomaly. Photochemical irradiation of sulfur gaseous species in the early solar nebula has, most likely, produced this anomaly. Observations of mass independent sulfur of photochemical origin suggest that chondrules and their rims must have formed in an optically thin nebular region. This also suggests that the chondrules were formed near the protoSun when it was active in ultraviolet light emission. © 2006 Elsevier Inc. All rights reserved.
Keywords: chondrites